Sharia global trade and sustainable economic growth: A narrative review of justice principles and ethical business - Kholis, Nur; Bariroh, Arrizqah (Privietlab, 2025)
This study seeks to combine and assess the current body of work on the integration of Shariah principles into international trade and their potential contribution to sustainable economic growth. Utilizing a narrative review approach, this study synthesizes academic papers, books, policy documents, and case studies published between 2018 and 2025. A thematic analysis was conducted to explore the correlation between Shariah principles and such as justice (al-ʿadl), transparency (al-shafāfiyyah), the prohibition of riba, gharar, and maysir, and compliance with halal and thayyib standards—and the United Nations Sustainable Development Goals (SDGs), particularly SDG 8 (inclusive growth), SDG 10 (reduced inequalities), SDG 12 (responsible consumption and production), and SDG 16 (peace, justice, and strong institutions). The findings indicate significant opportunities in the expanding halal market, innovations in blockchain halal supply chains, and the standardization of cross-border halal certification. Furthermore, examples from the Islamic Development Bank (IsDB) and Nestlé demonstrate that Shariah-compliant practices can improve fairness, market access, and social welfare while also highlighting challenges such as regulatory fragmentation, limited global awareness of Islamic economics, and infrastructure shortcomings. This study contributes to the creation of an integrated framework linking Shariah economic principles with SDG goals in international trade policy, providing a conceptual guide for policymakers, trade organizations, and multinational companies. Future research should focus on sector-specific empirical applications, develop quantitative models to evaluate the effects of Shariah-compliant trade on sustainable development outcomes, and investigate technological innovations to align Islamic economic ethics with global sustainability objectives.